Decreased flow-mediated dilatation in patients with rheumatoid arthritis: a meta-analysis. Issue 1099 (2nd November 2016) - Xu, Shu-Zhen; Wang, Peng; Guan, Shi-Yang; Li, Hong-Miao; Leng, Rui-Xue; Pan, Hai-Feng; Ye, Dong-Qing
ABSTRACT: Objectives: To derive a more precise comparison of flow-mediated dilatation (FMD%) of the brachial artery between patients with rheumatoid arthritis (RA) and normal controls by performing a meta-analysis of appropriate studies. Methods: PubMed and EMBASE databases were searched for all relevant articles. STATA (V.12.0) software was used to perform the meta-analysis. Quality estimation of all appropriate studies was evaluated according to the Newcastle-Ottawa Scale (NOS). Standardised mean difference (SMD) with 95% CIs were calculated with a random-effects model. The Cochrane Q test and I 2 statistic were used to evaluate the heterogeneity. Funnel plot and Egger's test were conducted to assess the publication bias. Results: In total, 464 articles were obtained after searching the two databases. Ten studies were included in the meta-analysis on the basis of the inclusion and exclusion criteria. Significant heterogeneity was observed among these 10 studies (Q=102.89, p<0.001, I 2 =91.3%) with random-effects modelling. The results showed that the RA group had significantly lower FMD% (SMD: −1.405; 95% CI −1.992 to −0.817; p<0.001) than the control group. Egger's test (p=0.004) indicated that the funnel plot showed a skewed or asymmetrical shape and publication bias existed. Sensitivity analyses suggested the robustness and credibility of our results. Conclusions: FMD% in patients with RA is significantly decreased compared with healthy controls. FMD% is an important early marker of atherosclerosis. It may be used as a parameter to forecast cardiovascular disease in patients with RA.